2021
DOI: 10.48550/arxiv.2108.10043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Studying the holographic Fermi surface in the scalar induced anisotropic background

Sayan Chakrabarti,
Debaprasad Maity,
Wadbor Wahlang

Abstract: Holographic properties of a finite density fermion system have been shown to exhibit many interesting behaviours which can be observed in future. In this paper, we study low energy fermion properties in the framework of holographic Mott-Insulator system. We study the nature of the Fermi surface and its evolution by tuning both Lorentz preserving and violating dipole coupling in the bulk. We further introduce translational symmetry breaking complex scalar field, which is assumed to couple with the holographic f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…In this section, we will briefly discuss about the Q-lattice since we had put a detail discussion in [47], we will highlight only few important points here. Here, the set up for the Qlattice background will be a (3 + 1)−dimensional gravity theory in the bulk that could be mapped to a dual theory at the boundary in (2 + 1)− dimensions.…”
Section: The Q-lattice Geometrymentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we will briefly discuss about the Q-lattice since we had put a detail discussion in [47], we will highlight only few important points here. Here, the set up for the Qlattice background will be a (3 + 1)−dimensional gravity theory in the bulk that could be mapped to a dual theory at the boundary in (2 + 1)− dimensions.…”
Section: The Q-lattice Geometrymentioning
confidence: 99%
“…Further, for fixed mass m 2 φ , we found that the solutions are specified in terms of three dimensionless parameters namely, T/µ , k/µ and χ (1) /µ α − , where T is the temperature of black hole. We showed some plots of the background solutions in our previous work [47] and we will use the same numerical background for analysis of the fermion spectral function later.…”
Section: The Q-lattice Geometrymentioning
confidence: 99%
See 3 more Smart Citations